2020
DOI: 10.3390/plants9050633
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Compounds and Photosynthesis in Passiflora Plant Leaves under Varying Light Intensities

Abstract: Functional constituents in the leaves of Passiflora plants contain antidepressant and antianxiety effects which are beneficial to human health and fitness. The objective of this study was to investigate leaf growth, physiological parameters, and secondary metabolite contents of Tainung No. 1 variety (P. edulis × P. edulis f. flavicarpa.) and P. suberosa in response to three light intensity conditions, including 100% light intensity (LI-100), 50% light intensity (LI-50), and 15% light intensity (LI-15) for 2 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Flavonoid biosynthesis is light-dependent. Higher light intensities stimulate the flavonoids synthesis in Passiflora suberosa L., which protects the plants from HL damage, as documented by Ni et al [ 290 ]. Moreover, Stewart et al [ 291 ] narrated about water-insoluble antioxidant carotenoids (the xanthophylls zeaxanthin and lutein as well as β-carotene), which maintain the higher growth rate in Lemna gibba L. even under very HL (700 µmol photons m −2 s −1 , 7 d).…”
Section: Antioxidant Metabolism and The Detoxification Of Ros Undementioning
confidence: 88%
“…Flavonoid biosynthesis is light-dependent. Higher light intensities stimulate the flavonoids synthesis in Passiflora suberosa L., which protects the plants from HL damage, as documented by Ni et al [ 290 ]. Moreover, Stewart et al [ 291 ] narrated about water-insoluble antioxidant carotenoids (the xanthophylls zeaxanthin and lutein as well as β-carotene), which maintain the higher growth rate in Lemna gibba L. even under very HL (700 µmol photons m −2 s −1 , 7 d).…”
Section: Antioxidant Metabolism and The Detoxification Of Ros Undementioning
confidence: 88%
“…The previous studies also indicated that chlorophyll could be synthesized only in light; thus, extending the photoperiod was beneficial for the synthesis of photosynthetic pigments [44]. In addition, Ni et al [45] indicated that the shading treatment (15% light intensity, 85% shaded) could promote Passiflora plant (Tainung No. 1) growth in SPAD compared with the non-shaded treatment, suggesting that long-term low-light-intensity treatment increased the relative chlorophyll concentration per leaf area in Passiflora plants.…”
Section: Impacts Of Supplementary Light Duration and Light Intensity On Photosynthetic Characteristics Of Cucumber Seedlingsmentioning
confidence: 98%
“…Moreover, there were clear increases in TF, OR, and IV content in 'Tainung 1' and 'P. suberosa' in LI-50 and LI-100 treatments compared to the LI-15 treatment (Ni et al, 2020). In the present study, temperature influences plant growth, Chl content, and different responses by bioactive compounds in HC leaves, information which can be used to optimize the growth and development of plants in controlled-temperature settings.…”
Section: Discussionmentioning
confidence: 51%